Redesign Kawasan Wisata Danau Raja Rengat Dengan Prinsip Arsitektur Berwawasan Lingkungan - M Shofyan; Wahyu Hidayat; Muhd Arief Al Husaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Indragiri Hulu has several tourist attractions that are already known by the people inside and outside Indragiri Hulu regency, especially Lake Raja which has its own specialty that is located in the center of Indragiri Hulu regency, namely rengat city. Raja Lake has great potential as a tourist icon of Indragiri Hulu regency. In addition to being located in the center of The Raja Lake Tourism district is also supported by a replica of the Malay Kingdom. The application of the theme of environmentally sound architecture to display the natural beauty of the Lake Raja area that will be applied to landscapes and buildings of the area in other words the design that still maintains and preserves the natural environment Redesign will later follow the rules of ecological architecture, Green Building, so that the Lake Raja Tourism Area becomes a tourist icon indragiri Hulu district that utilizes the surrounding natural environment conditions. Keywords : Eco Architecture, Tourist Areas, Malay